The effect of calcineurin inhibitors on anthropometric measurements in kidney transplant recipients - Emel Isiktas Sayilar; Alparslan Ersoy; Canan Ersoy; Aysegul Oruc; Yavuz Ayar; Deniz Sigirli (BMC Nephrology, 2022)
Abstract Background This study was designed to investigate the effect of calcineurin inhibitors (CNIs), cyclosporine (CsA), and tacrolimus (Tac) on anthropometrics in kidney transplant recipients. Methods 111 of 128 adult kidney transplant recipients who received post-transplant CNIs were included in this retrospective study. Anthropometrics were recorded in the pre-transplant and post-transplant 4-year follow-up periods (1st, 3rd, 6th, 12th, 24th, 36th and 48th months). Results Compared to pre-transplant values, significant increases in body weight and body mass index (between 3rd and 48th months), waist and hip circumferences (between 1st and 48th months), waist-to-hip ratio (between 1st and 3rd or 6th months) and neck circumference (between 1st and 12th or 24th months) were observed in both CsA and Tac groups. A significant increase was noted in post-transplant body fat percentage values for the 3rd to 24th months in the CsA group, whereas for the 24th to 48th months in both CsA and Tac groups. Hip circumferences percentage changes from the pre-transplant period to the 1st, 12th and 24th months were significantly higher in CsA than in the Tac group. At each time point, there was no significant difference in percentage changes for other anthropometric parameters between the CsA and Tac groups. De novo diabetes mellitus developed in 8.3% of the CsA group and 19.1% of the Tac group. Conclusions After a successful kidney transplant, anthropometric measurements increase in most recipients. Although the effect of calcineurin inhibitor type on weight gain is unclear, a regression analysis showed that CNI type was not a risk factor for the development of obesity in the 48th month. However, it is helpful to be cautious about its dyslipidemic effect in patients using CsA and the potential hazards of using Tac in patients with a diabetic predisposition.